Unilateral vocal cord immobility in a massive pericardial effusion secondary to lung carcinoma / Nur Saadah Mohamad ... [et al.] - Mohamad, Nur Saadah; Mohd Umbaik, Norsyamira Aida; Nik Hassan, Nik Fariza Husna; Wan Isa, Wan Yus Haniff; Mohamad, Irfan (Faculty of Medicine, 2022)
Ortner syndrome or cardiovocal syndrome is characterized by vocal cord immobility due to recurrent laryngeal nerve palsy resulted from a cardiovascular pathology. It is due to the compression of the recurrent laryngeal nerve along its pathway, from the enlargement of the pulmonary artery, aorta and dilatation of left atrium. We report a middle-aged lady presented with hoarseness after four months of breathlessness. Laryngoscopy revealed that left vocal cord immobility and computed tomography showed a globular-shaped heart with a lung mass and multiple mediastinal lymphadenopathies. We highlight the multiple possible causes for the Ortner syndrome in this case.